Free Banking in Sweden: The Case of Private Bank Notes, 1831-1902 - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2021)
This paper examines the Swedish record of competition in the supply of bank notes in the 19th century. Between 1831 and 1902, private commercial banks, organized as partnerships with unlimited liability for their owners, issued notes competing with the notes of the Riksbank, the bank owned by the Riksdag, the Swedish parliament. The private banks turned out to be competitive in this market despite several legal obstacles, most notably that private notes were never legal tender – only Riksbank notes were. The private note-issuing banks developed techniques to increase the distribution of their notes. No case of an overissue of notes or of runs by the public on private note banks occurred. No private bank failed to redeem its notes into Riksbank notes. Opinion in the Riksdag remained hostile to private bank notes, reflected in the gradual restriction of the denominations of the notes issued by private banks and in rising taxes on private notes. Eventually, the Riksdag gave its bank, the Riksbank, a monopoly of note issue in Sweden. The evidence from the Swedish experience of free banking suggests that the design of the legal system was the prime explanation for the successful performance of private notes.
Keywords: E42; E51; E58; G21; K20; N13; N23; 330; Free banking; central banking; private bank notes; unlimited liability; currency competition; Riksbank; Sweden